Agroforestry landscapes and global change: landscape ecology tools for management and conservation - Martínez Pastur, Guillermo José; Andrieu, Emilie; Iverson, Louis R.; Peri, Pablo Luis (Springer, 2019)
Forest ecosystems are impacted by multiple uses under the influence of global drivers, and where landscape ecology tools may substantially facilitate the management and conservation of the agroforestry ecosystems. The use of landscape ecology tools was described in the eight papers of the present special issue, including changes in forested landscapes due to agricultural and forestry activities, landscape changes due to recent intensification of agriculture, and the impacts of agroforestry as compared to natural forest ecosystems. Landscape ecology can improve the economic, environmental and social values of agroforestry, and this knowledge should help to develop new management alternatives for agroforestry. We believe that these papers will inform management at the landscape level, especially in agroforestry landscapes, offering new tools for management and conservation.